2024
DOI: 10.1021/acsestair.3c00063
|View full text |Cite
|
Sign up to set email alerts
|

Light Exposure of Wood Smoke Aerosol: Connecting Optical Properties, Oxidation, Radical Formation, and Chemical Composition

Carolyn Liu-Kang,
Anna Sokolova,
Yufeng Gong
et al.

Abstract: Biomass burning brown carbon (BrC) aerosol affects the climate by absorbing light in the visible and UV wavelengths, with daytime photochemistry changing its optical properties. Here, aging by UVB irradiation of BrC in both the aqueous and particle states was conducted to evaluate the conditions and mechanism required to change the ability of BrC to absorb light with an emphasis on the role of radicals and oxidation. Photoreactions enhanced visible light absorption with O 2 present in both the aqueous phase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…Previous studies have demonstrated that natural chromophoric dissolved organic matter (CDOM) possesses photosensitizing properties, enabling it to be promoted to a triplet state ( 3 CDOM*) after exposure to solar radiation in the aqueous phase or in the particle . The 3 CDOM* generated can subsequently participate in various photochemical processes, such as enhancing secondary organic aerosol (SOA) production through the adsorption of volatile organic compounds (VOCs), , promoting reactive oxygen species (ROS) production, reduction of NO 2 to HONO, and promoting photoenhancement of biomass burning brown carbon during aqueous and condensed-phase photolysis . We hypothesize that the photosensitizing capability of humic substances may play a role in the present work as they are known constituents of CDOM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that natural chromophoric dissolved organic matter (CDOM) possesses photosensitizing properties, enabling it to be promoted to a triplet state ( 3 CDOM*) after exposure to solar radiation in the aqueous phase or in the particle . The 3 CDOM* generated can subsequently participate in various photochemical processes, such as enhancing secondary organic aerosol (SOA) production through the adsorption of volatile organic compounds (VOCs), , promoting reactive oxygen species (ROS) production, reduction of NO 2 to HONO, and promoting photoenhancement of biomass burning brown carbon during aqueous and condensed-phase photolysis . We hypothesize that the photosensitizing capability of humic substances may play a role in the present work as they are known constituents of CDOM.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have examined the effect that light exposure has on the absorption spectra of particulate matter representing various types of organic aerosols. For example, both photobleaching and photoenhancement have been reported for water-soluble brown carbon from wood smoke, ,,, ambient biomass burning brown carbon, brown carbon from burning of urban construction material, and 4-nitrophenols during aqueous photolysis experiments. While the extent to which photolysis modifies these spectra varies, some of them demonstrate the same general pattern that we have observed with SRFA, namely photobleaching at shorter UV wavelengths and photoenhancement at longer visible wavelengths. , Thus, in this respect SRFA appears to be a good surrogate for organic aerosols.…”
Section: Resultsmentioning
confidence: 99%